Regeneration of Leadership Models in Islamic Boarding Schools: Khidmah-Based Integration for Administrative Efficiency - Samsudin Samsudin; Muhammad Saeful Amri; Ahmad Muflihin (Universitas Islam Sultan Agung, 2026)
Leadership regeneration in Islamic boarding schools (pesantren) does not always follow hereditary succession; it may also be organized through structured selection mechanisms grounded in noble religious values. One such mechanism is khidmah, the disposition of santri to dedicate themselves to service to the kiai as a means of deepening tafaqquh fi al-din while simultaneously preparing them for future leadership responsibilities. This tradition resonates with the broader orientation of Islamic education toward the internalization of values and the cultivation of leadership character. This study aims to (1) describe the philosophical foundation underlying leadership regeneration in pesantren, (2) construct a model of khidmah-based leadership regeneration, and (3) analyze how this model contributes to administrative efficiency in pesantren governance. Using a qualitative, phenomenological approach, data were collected through in-depth interviews, participant observation, and documentary review at Pondok Tahfizh Yanbu'ul Qur'an Putra Pusat in Kudus and Pondok Pesantren As-Salafi Al-Fitrah in Surabaya, both of which exhibit a distinctive approach to instilling leadership values through the khidmah tradition. The findings show that both pesantren employ a non-genealogical, criteria-based mechanism for appointing caretakers of their branch institutions, in which khidmah functions simultaneously as a vehicle for religious cadre formation and as an administrative instrument that distributes managerial authority across the domains of leadership, institutional governance, entrepreneurial skill, and pedagogy. This distribution of responsibility reduces institutional dependence on a single charismatic figure and strengthens the administrative sustainability of pesantren as they expand into multiple branches.